2014
DOI: 10.1080/13691058.2014.979885
|View full text |Cite
|
Sign up to set email alerts
|

‘Women at risk’: the health and social vulnerabilities of the regular female partners of men who inject drugs in Delhi, India

Abstract: Needle and syringe sharing is common among people who inject drugs and so is unprotected sex, which consequently puts their sex partners at risk of sexually transmitted infections (STIs) including HIV and other blood-borne infections, like hepatitis. We undertook a nested study with the regular female partners of men who inject drugs participating in a longitudinal HIV incidence study in Delhi, India. In-depth interviews were conducted with female partners of 32 men. The interviews aimed to gather focused and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The proportion of participants tested for HIV was high despite the perceived low risk of HIV. This approach may also have mitigated transport, administrative, attitudinal, and trust-related barriers which deter testing of people who use drugs in conventional health facilities [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of participants tested for HIV was high despite the perceived low risk of HIV. This approach may also have mitigated transport, administrative, attitudinal, and trust-related barriers which deter testing of people who use drugs in conventional health facilities [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings endorse the use of methadone to mitigate risks [ 41 , 42 ], and the use of community-based outreach model for providing integrated HIV and harm-reduction services [ 43 ]. Other studies have shown that the use of socially familiar infrastructure, such as community-based drop-in centers can act in synergy with the use of peer counsellors or educators or outreach workers to enhance HIV testing, entry into HIV care, and uptake of harm-reduction interventions [ 20 , 39 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of HIV among PWID combined with low levels of protective behaviors, 77.4% of PWID did not use a condom at last sex in 2014 [ 4 ]. As in other settings, the spouses of PWID also face substantial stigma and discrimination, which increases their vulnerability to HIV [ 5 , 6 ]. Latest estimates suggest that there are around 104 500 PWID in Pakistan and 60 to 65 thousand in Punjab and as many as 33.8% are married [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public health programs may also consider proactive outreach to women with injecting male partners as they have low perceived risk and inadequate agency to negotiate safe sex. 44…”
Section: Discussionmentioning
confidence: 99%